Evaluation of Candida albicans prevalence in mouth and Stafilococcus aureus prevalence in eye and nose in patients with Sjögren’s syndrome - İrfan Buğday; Tayfun Akalın; Selma Karagöz (Ulusal Romatoloji Dergisi)
Objective: Sjögren’s syndrome (SS) is a chronic, progressive and autoimmune disease characterized by the lymphocytic infiltration of the exocrine glands leading to dry eyes and dry mouth. The present study investigates the prevalence of Staphylococcus aureus (S. aureus) in the ophthalmic and nasal mucosa and Candida albicans (C. albicans) in the oral mucosa of patients with primary SS. Previous studies in the literature have included only a limited number of cases, while the present study includes 100 patients with primary SS patients, contributing to the achievement of more reliable results. This study aimed to show that the frequency of S. aureus and C. albicans is high in patients with SS. Methods: This study included patients diagnosed with primary SS based on the American-European Consensus Group criteria among those who presented to the outpatient Kayseri Training and Research Hospital, Clinic of Rheumatology between February 2016 and June 2016. Healthy volunteers without chronic diseases and without regular drug use among those who presented to the outpatient Kayseri Training and Research Hospital, Clinic of Internal Medicine were included in the study as a control group. Samples were collected from the nose (medial nasal mucosa of both nostrils), the mouth (buccal mucosa at the molar tooth level), and the conjunctival sac (with four swab rotations). Results: C. albicans growths were identified in 37% (n=37) and 17% (n=17) of the patient and control groups, respectively, based on oral culture evaluations. The difference between the two groups was statistically significant (p=0.001). S. aureus growth was identified in 12% (n=12) and 1% (n=1) of the patient and control groups, respectively, based on nasal culture evaluations, and the difference between the two groups was statistically significant (p=0.002). Conclusion: Infections are among the main causes of morbidity and mortality in rheumatological diseases. The most common reason for hospital visits has been reported as infections associated with rheumatoid arthritis, systemic lupus erythematosus, and other rheumatological diseases. The involvement of SS in the exocrine glands leads to dysfunction and decreased secretions, resulting in dry mouth, dry eyes, and dry skin. As a result of these changes in SS, the colonization of both normal flora and unassociated pathogenic bacteria increases, contributing to a higher frequency of infections. In our study the prevalence of S. aureus in the nasal mucosa and C. albicans in the oral mucosa of primary SS patients was statistically significantly higher than in healthy controls.